Advances in breast cancer treatment: a systematic review of preoperative stereotactic body radiotherapy (SBRT) for breast cancer - Mateusz Bilski; Katarzyna Konat-Bąska; Maria Alessia Zerella; Stefanie Corradini; Marcin Hetnał; Maria Cristina Leonardi; Martyna Gruba; Aleksandra Grzywacz; Patrycja Hatala; Barbara Alicja Jereczek-Fossa; Jacek Fijuth; Łukasz Kuncman (Radiation Oncology, 2024)
Abstract Breast conserving treatment typically involves surgical excision of tumor and adjuvant radiotherapy targeting the breast area or tumor bed. Accurately defining the tumor bed is challenging and lead to irradiation of greater volume of healthy tissues. Preoperative stereotactic body radiotherapy (SBRT) which target tumor may solves that issues. We conducted a systematic literature review to evaluates the early toxicity and cosmetic outcomes of this promising treatment approach. Secondary we reviewed pathological complete response (pCR) rates, late toxicity, patient selection criteria and radiotherapy protocols. We retrieved literature from PubMed, Scopus, Web of Science, Cochrane, ScienceDirect, and ClinicalTrials.gov. The study adhered to the PRISMA 2020 guidelines. Ten prospective clinical trials (7 phase II, 3 phase I), encompassing 188 patients (aged 18–75 years, cT1-T3 cN0-N3 cM0, primarily with ER/PgR-positive, HER2-negative status,), were analyzed. Median follow-up was 15 months (range 3–30). Treatment involved single-fraction SBRT (15-21Gy) in five studies and fractionated (19.5–31.5Gy in 3 fractions) in the rest. Time interval from SBRT to surgery was 9.5 weeks (range 1–28). Acute and late G2 toxicity occurred in 0–17% and 0–19% of patients, respectively, G3 toxicity was rarely observed. The cosmetic outcome was excellent in 85–100%, fair in 0–10% and poor in only 1 patient. pCR varied, showing higher rates (up to 42%) with longer intervals between SBRT and surgery and when combined with neoadjuvant systemic therapy (up to 90%). Preoperative SBRT significantly reduce overall treatment time, enabling to minimalize volumes. Early results indicate excellent cosmetic effects and low toxicity. Graphical abstract